p53 expression in normal paraffin-embedded tissue using different antibodies and antigen retrieval buffer systems. - Pillai, G; Roberts, H; Gatter, K; Pezzella, F (2003)
AIMS: The study was undertaken to demonstrate wild-type p53 in normal paraffin-embedded tissues using two widely used antibodies, DO7 and 1801 and two different antigen retrieval buffer systems. METHODS AND RESULTS: Formalin-fixed paraffin-embedded normal tissue samples were obtained from the archives of the John Radcliffe Hospital, Oxford. Antigen retrieval was performed by microwaving using two different buffer systems: (i) the commercially available Dako target retrieval solution (Cat. no. 1699) (pH 9.8-9.9), (ii) freshly prepared buffer consisting of 0.1 m EDTA with 0.1% Tween pH 6.0, and (iii) freshly prepared buffer consisting of 0.1 m EDTA with 0.1% Tween pH 8.0. Staining was performed with DO7 and 1801 antibodies using the Dako Envision kit (peroxidase/DAB). DO7 antibody elicited strong nuclear staining in the mucosal cells of the small and large intestine, lymphoid cells, decidua, neurones such as Purkinje cells of the cerebellum, glandular epithelial cells and stromal cells of the prostate, cardiac myocytes and bronchial epithelial cells. Cytoplasmic staining was noted in Purkinje cells, glandular epithelium of prostate, exocrine pancreas and renal tubular epithelium. The 1801 antibody did not produce staining in any of these tissues. CONCLUSIONS: Our study demonstrates the presence of p53 in normal paraffin-embedded tissue with nuclear and/or cytoplasmic localization in some instances. In our view, DO7 appears to be better suited for such detection.